2010
DOI: 10.1177/0020872809359751
|View full text |Cite
|
Sign up to set email alerts
|

The changing context of China: Emerging issues for school social work practice

Abstract: This article provides a contextualized analysis of the ways in which school social workers may address the impact of economic, social and political challenges as they will be experienced by the children of mainland China, and how the profession of school social work may serve to ameliorate the negative effects on children as they transition through these developments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“….social injustices exist and to provide an opportunity for all children to optimize their educational potential'. Levine and Zhu (2010) in discussing the Chinese context suggest that 'the role of school social work is to ensure the optimum fit between the student and his/her environment, through intervention at the interface of the ecological levels'. (p. 340).…”
Section: Literaturementioning
confidence: 99%
“….social injustices exist and to provide an opportunity for all children to optimize their educational potential'. Levine and Zhu (2010) in discussing the Chinese context suggest that 'the role of school social work is to ensure the optimum fit between the student and his/her environment, through intervention at the interface of the ecological levels'. (p. 340).…”
Section: Literaturementioning
confidence: 99%
“…The school change model encountered bottlenecks because the school reform was bound to affect their own interests (Levine and Zhu, 2010).…”
Section: School Change Modelmentioning
confidence: 99%
“…However, accompanied with these changes, there has also been a disintegration of traditional family and social-supportive networks (e.g. divorce rates have risen from 0.07% in 1990 to 0.17% in 2008 [ 1 ]), contributing to greater stress among children and adolescents [ 2 ]. In a meta-analysis of 40 studies, self-reported anxiety levels were observed to have increased 0.7 standard deviations from 1992 to 2005, and anxiety levels were positively correlated with the Gini coefficient, divorce rate, unemployment rate, and crime rate [ 3 ].…”
Section: Introductionmentioning
confidence: 99%